Research Progress on the Pathogenesis of Knee Osteoarthritis - Du, Xin; Liu, Zi‐yu; Tao, Xing‐xing; Mei, Yong‐liang; Zhou, Da‐qian; Cheng, Kang; Gao, Si‐long; Shi, Hou‐yin; Song, Chao; Zhang, Xiao‐min (Orthopaedic surgery, 2023)
Knee osteoarthritis (KOA) is a chronic joint bone disease characterized by inflammatory destruction and hyperplasia of bone. Its main clinical symptoms are joint mobility difficulties and pain, severe cases can lead to limb paralysis, which poses major pressure to the quality of life and mental health of patients, but also brings serious economic burden to society. The occurrence and development of KOA is influenced by many factors, including systemic factors and local factors. The joint biomechanical changes caused by aging, trauma and obesity, abnormal bone metabolism caused by metabolic syndrome, the effects of cytokines and related enzymes, genetic and biochemical abnormalities caused by plasma adiponectin, etc. all directly or indirectly lead to the occurrence of KOA. However, there is little literature that systematically and comprehensively integrates macro‐ and microscopic KOA pathogenesis. Therefore, it is necessary to comprehensively and systematically summarize the pathogenesis of KOA in order to provide a better theoretical basis for clinical treatment. Macroscopic factors affecting the occurrence and development of knee osteoarthritis.